2005
DOI: 10.1128/iai.73.2.859-864.2005
|View full text |Cite
|
Sign up to set email alerts
|

The M Protein Is Dispensable for Maturation of Streptococcal Cysteine Protease SpeB

Abstract: The streptococcal pyrogenic exotoxin B (SpeB) is an important virulence factor of group A streptococci (GAS) with cysteine protease activity. Maturation of SpeB to a proteolytically active form was suggested to be dependent on cell-wall-anchored M1 protein, the major surface protein of GAS (M. Collin and A. Olsén, Mol. Microbiol. 36:1306-1318, 2000). Collin and Olsén showed that mutant GAS strains expressing truncated M protein secrete a conformationally different form of unprocessed SpeB with no proteolytic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…Protein preparations were tested at least twice. Parallel assays were performed with addition of 10 M of cysteine protease inhibitor E64 (Sigma) to confirm the specificity (30).…”
Section: Methodsmentioning
confidence: 99%
“…Protein preparations were tested at least twice. Parallel assays were performed with addition of 10 M of cysteine protease inhibitor E64 (Sigma) to confirm the specificity (30).…”
Section: Methodsmentioning
confidence: 99%
“…The 1.7-fold reduction in SpeB activity of the ⌬prtF2 mutant, relative to the parent strain, is statistically significant. The possibility exists that attenuation of the ⌬prtF2 mutant is ultimately due to a defect in the formation of enzymatically active SpeB (7,46). Yet, the ALAB49 ⌬prtF2 mutant expresses levels of cysteine protease activity comparable to those of its close genetic relative, the wt 29487 strain (33.9 U/ml), which, like wt ALAB49, is highly virulent in the hu-skin SCID mouse via a SpeB-dependent mechanism (27,37).…”
Section: Figmentioning
confidence: 99%
“…Others have shown that a peptidyl-prolyl isomerase, RopA, (29) and the serine protease, HtrA, (28) were necessary for proteolytic cleavage of the SpeB zymogen to the active protease. Still others have shown that M protein on the streptococcal surface is needed for the maturation of SpeB (10), but other investigators disagree (42).…”
mentioning
confidence: 99%